The Collective Bargaining Agreement: Its Nature and Scope - Charles O. Gregory (Washington University Law Quarterly, 1949)
In this Article I shall discuss some of the aspects of collective bargaining and labor agreements as these things look to a law professor.
Keywords: Labor law; Collective bargaining; Strikes and lockouts; Strikes and boycotts